The Relationship Between Dividend Payout and Economic Policy Uncertainty (Epu), Ownership Concentration and Free Cash Flow in Chile - Espinosa-Mendez, C (Taylor and Francis Ltd., 2023)
This study examines how the dividend payout of Chilean firms is associated with economic policy uncertainty (EPU), while controlling for ownership concentration and free cash flow, to consider agency problems. Its contribution is twofold. First, it detects a non-linear, U-shaped relation between EPU and dividend payout, which is a novel finding. Second, this result holds only in cases of high EPU. No significant relationship in cases of low EPU was detected. The sample comprises an unbalanced panel data of 1034 observations from 2005 to 2016. Including ownership concentration as an independent variable leads to a negative association between it and dividend payout, showing a potential agency problem between the main shareholder and the minorities. If free cash flow is considered in the model, then the results show a positive relation between free cash flow and dividend payout, which implies the mitigation of the agency problem. Finally, once both variables (ownership concentration and free cash flow) are considered together as explanatory variables, only free cash flow turns out to be statistically significant and positively associated with dividend payout. © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.